Financial Leverage, Risiko Sistematis, Size, Likuiditas Dan Return On Investment Pada Emiten LQ45 Di Bursa Efek Indonesia - Indah Masri; Salis Musta Ani (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2015)
The aims of these research is to examine the extent which the variables are identified (size, liquidity, and return on investment) influence the sensitivity of the relationship between financial leverage with systematic risk (beta) using data pool balance panel. This study used a sample LQ45 companies selected by certain criteria. Data taken from information the annual financial statements and annual reports LQ45 2010 to 2013 with a total of 92 firm-year observations. Through the test model 1, the result that size a significant positive effect on the level of 5%. While testing the model 2 showed significant positive results at the level of 1% for financial leverage and liquidity variable. Testing model 3 shows that the leverage significant positive effect on the level of 1%. When tested together in the fourth model, the significant variable is the incremental variable on moderation financial leverage with liquidity, and moderation financial leverage with ROI. Results of model 4 explains that the liquidity and investment levels can affect the level of risk. the higher the level of investment, it will weaken the effect of financial leverage on a systematic risk, due to the higher level of investment led to financial leverage will be decreased so that the inherent systematic risk will also be reduced.